Relationship between Oil Price and Macroeconomic Indicators in Russia - A. Yu. Mikhailov; D. B. Burakov; V. Yu. Didenko (Финансы: теория и практика, 2019)
One of the most important external factors affecting the exchange rate of the US dollar to the Russian rouble has been the global oil price. Russia, whose economy is mainly associated with oil production, is one of the world’s largest oil suppliers. Therefore, the slightest fluctuations in oil prices can have a significant effect on its economy. The aim of the article is to study the relationship between macroeconomic parameters and oil prices. The objectives of the study are to identify factors having a long-term positive relationship with oil prices based on a mathematical approach, as well as to propose improvements for Russian macroeconomic indicators. The authors use modern mathematical methods of vector autoregression (VAR-model), the Granger method and the Dickey-Fuller test to study the long-term and shortterm relationships between the relevant time series for the period from 2014 to 2016. On this basis, it was calculated that a 1% increase in GDP leads to a strengthening of the national currency by 1.47%. This fact can be explained by the overall growth of the national economy. The Granger test results for the model show that global oil price (and Russian GDP) has the greatest impact on the exchange rate in the short term. The following actions are proposed for improving macroeconomic indicators: stabilisation of foreign economic policy; diversification of exports (although oil revenues can serve as a tool for improving the quality of Russian economic development and public life in general); development of the Russian ‘Urals’ benchmark and increasing its trading volumes on the world market; transition to rubles for settlements of Russian oil and gas; use of a ruble indicator (ruble barrel) of the ‘Urals’ oil price to support the development of Russia’s financial and economic policy.